Analisis Service Quality Terhadap Kepuasan Penumpang pada Masa Pendemi Covid-19 di Bandar Udara Sultan Babullah Ternate - Nurjihana S A Samiun; Djoko Widagdo (Jurnal Multidisiplin Madani, 2022)
Service quality is the act of success of a company that can and is able to form a positive perception based on the expectations of its customers and is able to create a satisfaction and loyalty of its customers. service affects passenger satisfaction during the corona virus-19 pandemic at Sultan Babullah airport in Ternate. This research method uses quantitative methods with data collection techniques using questionnaires and requires a sample of 100 selected respondents selected using Non-Probability Sampling with Incidental Sampling Techniques. The results showed that the service quality variable (X) had a significant effect on the passenger satisfaction variable (Y) of 88.7%. The remaining 11.3% is influenced by other variables outside the variables not studied.